2014
DOI: 10.4238/2014.april.30.4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical application of carbon nanoparticle lymph node tracer in the VI region lymph node dissection of differentiated thyroid cancer

Abstract: ABSTRACT. The application and clinical significance of carbon nanoparticle lymph tracer in the VI region (central region) lymph node dissection of differentiated thyroid cancer was investigated. Eighty patients with differentiated thyroid cancer were equally divided into the carbon nanoparticle-marked group (ipsilateral thyroid injection) and the control group (no injection). All patients underwent standard primary tumor treatment and VI lymph node dissection. The number of lymph nodes retrieved in the carbon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 2 publications
2
20
1
Order By: Relevance
“…The authors concluded that the CNs method better aided the screening and selection of patients who are most likely to benefit from cervical lymph node dissection (37). CNs stain the majority of lymph nodes, with the reported rate of CN staining was 69.89-95.26% (20,37,38), with the black-staining rate in the present study being 84.90%. More lymph nodes <5 mm were detected with the assistance of CNs, which cannot be easily recognized without any assistance.…”
Section: Discussionsupporting
confidence: 45%
“…The authors concluded that the CNs method better aided the screening and selection of patients who are most likely to benefit from cervical lymph node dissection (37). CNs stain the majority of lymph nodes, with the reported rate of CN staining was 69.89-95.26% (20,37,38), with the black-staining rate in the present study being 84.90%. More lymph nodes <5 mm were detected with the assistance of CNs, which cannot be easily recognized without any assistance.…”
Section: Discussionsupporting
confidence: 45%
“…Hence, the number of metastatic lymph nodes in the CN group was statistically higher than that in the blank control group. Besides, 4 studies reported that the number of retrieved small lymph nodes (diameter <5 mm) was significantly higher in the CN group 44,60,61,67. These findings suggest that CNs may help identify tiny, suspicious lymph nodes.…”
Section: Resultsmentioning
confidence: 91%
“…According to the search strategy, 149 references were obtained, and 47 RCTs met the inclusion criteria 18,19,2367. The flowchart of the literature search is shown in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…[611] In recent years, they are commonly used as intraoperative localization for thyroid cancer, which would bring extraoperative procedure. [12,13] Preoperative ultrasound-guided CNs localization will improve this disadvantage. Therefore, we conducted a retrospective cohort study to evaluate the effectiveness and safety of reoperative ultrasound-guided CNs localization.…”
Section: Introductionmentioning
confidence: 99%